Management of Continuous Professional Development through Competency-Based Training Model for Junior High School Teachers - . Sherly; Syawal Gultom; Eka Daryanto; . Nasrun (Ital Publication, 2023)
One of the strategies to improve teachers' skills and professionalism is the practice of continuous professional development. To fulfill the demands of students and learning in the 21st century, teachers must have a strong foundation and knowledge of ongoing professional development. However, a-business-as-usual continuous professional development does not contribute to any significant improvements for teachers of junior high school in Pematangsiantar. The objective of this research was to develop a management model for teachers’ continuous development. This is carried out through competency-based training with a heutagogy approach. A development model called ADDIE, which stands for Analysis, Design, Develop, Implementation, and Evaluation was used to develop the management model. The subject of this research was 80 junior high school students in Pematangsiantar. They were divided into 30 and 50 people for the limited trial and the broad trial, respectively. Questionnaires were distributed as the instrument of data collection. The data was then analyzed using a statistical descriptive analysis technique. The research found that the effectiveness of the competency-based training management model was measured by the N-Gain score, in which the G-value was 0.79 and 0.82 for limited trial and broad trial, respectively, which was in the high category. The results of the assessment of the effectiveness of the model obtained an average value of 94%, which was in the